Evaluating the Development of the Integration if Emerging Economies Under the New İnternational Economy, the BRICS Group as A Model - Munaf Marza Neama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rapid economic and political rise of emerging countries has led to a change in the dynamics of power in the global system, as economic blocs have provided an important developmental role in the international economy.